Cumulative non-HDL-cholesterol burden in patients with hypertriglyceridemia receiving long-term fibrate therapy: Real life data from a lipid clinic cohort - Meral Kayıkçıoğlu; Shafa Shahbazova; Firdovsi İbrahimov; Levent Hürkan Can (KARE Publishing, 2020)
Objective: Though epidemiological data suggest that an elevated triglyceride (TG) level may be a risk factor for coronary artery disease (CAD), there is still insufficient clinical evidence. This study was designed to evaluate the real-life efficacy and side effects of fibrate treatment for hypertriglyceridemia seen in a lipid clinic, as well as cardiovascular and diabetic outcomes. Methods: This retrospective study evaluated patients who were followed-up for a diagnosis of hypertriglyceridemia at the lipid outpatient clinic of the Ege University Cardiology Department between 1997 and 2018. Data of demographic and clinical characteristics were obtained from hospital records. All patients (n=240) with at least 1 year of follow-up were included in the analysis. During follow-up, patients were treated with fenofibrate, and less frequently, gemfibrozile (14 patients), at different doses according to the TG level and disease severity. Results: Of the study population, 23% had CAD, 21% were diabetic, and 52% were obese. On admission, 20% were using fibrates and 17% were on statins. The mean admission lipid levels were TG: 281+-194 mg/dL, low-density lipoprotein cholesterol: 115+-37 mg/dL, high-density lipoprotein (HDL) cholesterol: 43+-13 mg/dL, and non-HDL cholesterol: 166+-42 mg/dL. The mean length of follow-up was 5.3+-4.7 years (range: 1-16 years). A total of 8 (4.3%) patients had adverse effects during follow-up (1 on statin combination and 7 on fibrates alone). The side effects observed were an elevation of liver enzymes in 3, myalgia in 2, insomnia in 1, malaise in 1, and a skin rash in 1 patient. No rhabdomyolysis or myopathy was seen. During follow-up, diabetes developed in 14 and cardiovascular disease (CVD) in 14 patients. The cumulative non-HDL cholesterol level was significantly high in patients who developed diabetes or CVD. Receiver operating curve analysis indicated that a cumulative non-HDL cholesterol value of 1016 mg/dL was predictive of the development of diabetes mellitus or CVD with 85% sensitivity and 70% specificity. Conclusion: In real life, long-term fibrate use is effective and safe. The cumulative non-HDL cholesterol burden can be used to assess the efficacy of treatment as a simple and easily calculated method. Large studies are needed to further clarify the value of this parameter in predicting the development of both diabetes and CVD.